Elements de la terminologie du temps en egyptien ancien : une etude de semantique lexicale en diachronie - Chantrain, Gaelle, (Lingua aegyptia. Studia monographica ;, 2020)
This book has a double scope: first, bringing a contribution to the knowledge and understanding of the time conceptions in Ancient Egypt through a lexical study and, second, contributing to the definition of a methodological frame for lexical semantics in Ancient Egyptian.0In the introduction, the reader will first find a state of the art from the point of view of time-related studies in Egyptology, lexical semantics studies, and classifiers studies. The next introductory sections deal with the links between time, space and motion, with the complexity of time conceptions in Ancient Egypt, and with the impact of this plural vision on the lexicon.0The first part of the core study aims at establishing a proposition of canvas for the semasiology of nouns. It also presents the semasiological analysis of eight lexemes belonging to the unbounded time domain: #.t (moment), wnw.t (hour), nw (moment), tr (time), H#w (epoch), rk (epoch), oHow (lifetime) and Hnty (period).0The second part is dedicated to the onomasiology of the unbounded time domain, as well as some of its connections with some contiguous domains like space.